New insights on Noonan syndrome's clinical phenotype: a single center retrospective study - Francesco Baldo; Alice Fachin; Beatrice Da Re; Elisa Rubinato; Marco Bobbo; Egidio Barbi (BMC, 2022)
Abstract Background Noonan syndrome (NS) is a clinically and genetically heterogeneous disorder. Since its clinical phenotype is often mild and difficult to differentiate from other syndromes, its diagnosis can be challenging and its prevalence in the pediatric population is most certainly underestimated. The difficulty in identifying Noonan syndrome is also increased by the fact that genetic tests are currently not able to detect an underlying mutation in around 10% of the cases. Methods This is a retrospective, observational study conducted at the Institute for Maternal and Child "Burlo Garofolo" in Trieste, Italy. We recruited all the patients with clinical and/or genetic diagnosis of NS who were evaluated at the Department of Pediatrics between October 2015 and October 2020. Statistical analyses were performed with IBM SPSS Statistics software. The association between discrete variables has been evaluated through chi-squared test, indicating statistically significant p with Pearson test or Fischer test for variables less than 5. Results We recruited a total of 35 patients affected by Noonan syndrome. In 24 patients (75%) we identified an underlying genetic substrate: 17 patients had a mutation on PTPN11 (61%), 2 in SOS1, KRAS and SHOC2 (7% each) and only 1 in RAF1 (4%). 25% of the subjects did not receive a genetic confirm. As for the phenotype of the syndrome, our study identified the presence of some clinical features which were previously unrelated or poorly related to NS. For example, renal and central nervous system abnormalities were found at a higher rate compared to the current literature. On the contrary, some features that are considered very suggestive of NS (such as lymphatic abnormalities and the classical facial features) were not frequently found in our population. Conclusions In our analysis, we focused on the main phenotypic features of NS, identifying various clinical manifestation that were not associated with this genetic condition before. This could be helpful in raising the knowledge of NS's clinical spectrum, facilitating its diagnosis.